The red badge of courage - Crane, Stephen 1871-1900 (Great illustrated classics, 1993)
In the spring of 1863, while engaged in the fierce battle of Chancellorsville in Virginia, a young Union soldier matures to manhood and finds peace of mind as he comes to grips with his conflicting emotions about war.